Improved survival in patients with FDG-PET/CT-based radiotherapy treatment planning for squamous cell anal cancer - Lohynska, R; Mazana, E; Novakova-Jiresova, A; Jirkovska, M; Nydlova, A; Veselsky, T; Malinova, B; Buchler, T; Stankusova, H (Neoplasma, 2020)
The aim of this retrospective analysis was to evaluate the impact of FDG-PET/CT-based target volume definition on locoregional control and survival, compared to conventional CT-based target volume definition and dose prescription. One hundred and twenty-two patients with squamous cell anal cancer were treated with curative radiotherapy (RT) alone (27%) or with RT with concurrent chemotherapy (73%) and analyzed. Forty-six percent had the early disease (stage I+II) and 54% were stage III. FDG-PET/CT-based staging was performed in 21% of the patients. The mean follow-up time was 60 months. Other risk factors affecting survival were investigated. According to initial staging in both groups (FDG-PET/CT and conventional CT) were 10% of stage IV disease, and they were excluded from radical radiotherapy and treated with palliative intent. Ninety-two percent of the patients achieved complete remission. Significant favorable factors in univariate analysis associated with disease-free survival (DFS) were PET/CT staging, T1/2 and N0 stage, and clinical stage I and II. Locoregional control (LRC) correlated with the T1/2 stage and initial performance status (PS) 0. There were no significant factors affecting overall survival (neither in univariate nor multivariate analysis). In multivariate analysis, the factor associated with better DFS was PET/CT staging and for LRC, PS 0 and concomitant chemoradiation. Acute toxicity was increased in the concurrent chemo-radiotherapy group. Two-, five- and ten-year overall survival rates were 83%, 69%, and 60%; disease-free survival rates were 76%, 73%, 73%; local control rates were 91%, 90%, and 90% and colostomy-free survival was 89%, 86%, and 81%, respectively. PET/CT staging allowed targeted dose escalation to the primary tumor and nodal metastases while decreasing dose to uninvolved regions, resulting in significantly improved DFS without compromising locoregional control.
Keywords: Anus Neoplasms; retrospektivní studie; Neoplasm Staging; staging nádorů; Humans; Neoplasms, Squamous Cell; skvamocelulární nádory; lidé; radiofarmaka; Positron Emission Tomography Computed Tomography; Retrospective Studies; PET/CT; nádory anu; Radiopharmaceuticals